2017
DOI: 10.1002/2017jd027366
|View full text |Cite
|
Sign up to set email alerts
|

Do Lateral Flows Matter for the Hyperresolution Land Surface Modeling?

Abstract: Hyperresolution land surface modeling provides an unprecedented opportunity to simulate locally relevant water and energy cycle, but lateral surface and/or subsurface flows that are essential at fine scale are often neglected by most one‐dimensional land surface models (LSMs). To analyze effects of lateral flows across scales, a Conjunctive Surface‐Subsurface Process model, which considers soil moisture‐surface flow interaction and quasi‐three‐dimensional subsurface flow, is implemented over a mountainous Hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 45 publications
(68 reference statements)
2
66
0
Order By: Relevance
“…The comparison between CSSPv2 simulations driven by GLDAS1 and high‐resolution forcings (red bars) shows the importance of meteorological forcings in soil moisture simulation (Figure ). This is also consistent with our previous study, where gradual improvements were found by incorporating high‐resolution meteorological and surface data information (Ji et al, ). In short, high‐resolution forcing data are critical for a successful high‐resolution land surface modeling.…”
Section: Validation Of Csspv2 Over the Sanjiangyuan Regionsupporting
confidence: 93%
See 3 more Smart Citations
“…The comparison between CSSPv2 simulations driven by GLDAS1 and high‐resolution forcings (red bars) shows the importance of meteorological forcings in soil moisture simulation (Figure ). This is also consistent with our previous study, where gradual improvements were found by incorporating high‐resolution meteorological and surface data information (Ji et al, ). In short, high‐resolution forcing data are critical for a successful high‐resolution land surface modeling.…”
Section: Validation Of Csspv2 Over the Sanjiangyuan Regionsupporting
confidence: 93%
“…The LSM used in this study is the Conjunctive Surface-Subsurface Process (CSSP) model (Ji et al, 2017;Liang et al, 2012;Yuan & Liang, 2011). The CSSP model was developed from the Common Land Model (Dai et al, 2003(Dai et al, , 2004, but it has better representations in lateral surface and subsurface hydrological processes and their interactions (Choi et al, 2013).…”
Section: The Conjunctive Surface-subsurface Process Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The T&C model simulates lateral surface and subsurface water flows, which are currently neglected in many land surface models. Recent studies showed that models incorporating these processes (e.g., Ivanov et al, ) can simulate the heterogeneity of water and energy fluxes more realistically (Ji, Yuan, & Liang, ; Maxwell & Condon, ). This model advantage is reflected in the simulated patterns of soil effective saturation and subsequently on the spatial patterns of transpiration, LAI, and NPP (Figures , , S6, S7, and S8).…”
Section: Discussionmentioning
confidence: 99%